Aulacidae of the southwestern United States, Mexico, and Central America (Hymenoptera). - Smith, David R. (Contributions to Entomology = Beiträge zur Entomologie, 2008)
Forty-two species of Aulacidae are recorded from the southwestern United States (southern Texas, New Mexico, Arizona), Mexico, and Central America, including 11 species of Aulacus Jurine and 31 species of Pristaulacus Kieffer. Eight species are known from southwestern United States, 27 from Mexico, one from Guatemala, three from Honduras, one from Nicaragua, 11 from Costa Rica, and two from Panama. Taxa included are: Aulacus maculosus, n. sp. (Costa Rica); A. ochreus Smith, 2005 (Costa Rica); A. fascius, n. sp. (Mexico); A. veracruz, n. sp. (Mexico); A. costaricensis, n. sp. (Costa Rica); A heredia, n. sp. (Costa Rica), A. elongatus, n. sp. (Panama, Costa Rica); A. leon, n. sp. (Mexico); A. whartoni, n. sp. (Mexico); A. aneurus Walkley, 1952 (US: New Mexico); A. dispilis Townes, 1950 (US: Texas); Pristaulacus argutus, n. sp. (Mexico); P. tria, n. sp. (Costa Rica); P. maculatus (Schletterer, 1889) (Costa Rica, Nicaragua, Panama); P. ruficollis (Cameron, 1887) (Guatemala, Honduras, Mexico); P. auricomus, n. sp. (Honduras, Mexico, US: Arizona); P. virga, n. sp. (Mexico); P. punctum, n. sp. (Costa Rica); P. decorus, n. sp. (Mexico); P. aquilus, n. sp. (Mexico); P. torridus (Bradley, 1908) (US: Texas); P. anteala, n. sp. (Costa Rica); P. triclora, n. sp. (Mexico); P. nigricoxae, n. sp. (Mexico); P. unimacula, n. sp. (Mexico); P. postala, n. sp. (Mexico); P.stangei, n. sp. (Mexico); P. tenuis, n. sp. (Mexico); P. decolorus, n. sp. (Mexico); P. singulus, n. sp. (Costa Rica); P. candidus, n. sp. (Mexico); P. omninoniger, n. sp. (Mexico); P. townesi, n. sp. (Mexico), P. arizonicus (Townes, 1950) (US: Arizona); P. rufitarsis (Cresson, 1864) (US: Arizona, California, New Mexico); P. ruficruris, n. sp. (Mexico, US: Texas); P. parkeri, n. sp. (Mexico); P. mexiuni, n. sp. (Mexico, US: Arizona, Texas); P. totoferrugineus, n. sp. (Mexico); P. hespenheidei, n. sp. (Mexico); P. tamaulipas, n. sp. (Mexico); P. annulatus Kieffer, 1911 (Mexico). Aulacus hyalinipennis Westwood, 1841, is placed in species incertae sedis of Aulacidae.Keywordsparasitic wasps, Arizona, Texas, New Mexico, Mexico, Guatemala, Honduras, Nicaragua, Costa Rica, Panama, Cerambycidae, Buprestidae.Nomenclatural Actscostaricensis Smith, 2008 (Aulacus), spec. n.elongatus Smith, 2008 (Aulacus), spec. n.fascius Smith, 2008 (Aulacus), spec. n.heredia Smith, 2008 (Aulacus), spec. n.leon Smith, 2008 (Aulacus), spec. n.maculosus Smith, 2008 (Aulacus), spec. n.veracruz Smith, 2008 (Aulacus), spec. n.whartoni Smith, 2008 (Aulacus), spec. n.anteala Smith, 2008 (Pristaulacus), spec. n.aquilus Smith, 2008 (Pristaulacus), spec. n.argutus Smith, 2008 (Pristaulacus), spec. n.auricomus Smith, 2008 (Pristaulacus), spec. n.candidus Smith, 2008 (Pristaulacus), spec. n.decolorus Smith, 2008 (Pristaulacus), spec. n.decorus Smith, 2008 (Pristaulacus), spec. n.hespenheidei Smith, 2008 (Pristaulacus), spec. n.mexiuni Smith, 2008 (Pristaulacus), spec. n.nigricoxae Smith, 2008 (Pristaulacus), spec. n.omninoniger Smith, 2008 (Pristaulacus), spec. n.parkeri Smith, 2008 (Pristaulacus), spec. n.postala Smith, 2008 (Pristaulacus), spec. n.punctum Smith, 2008 (Pristaulacus), spec. n.ruficollis (Cameron, 1887) (Pristaulacus), Lectotype described as Aulacus ruficollisruficruris Smith, 2008 (Pristaulacus), spec. n.singulus Smith, 2008 (Pristaulacus), spec. n.stangei Smith, 2008 (Pristaulacus), spec. n.tamaulipas Smith, 2008 (Pristaulacus), spec. n.tenuis Smith, 2008 (Pristaulacus), spec. n.totoferrugineus Smith, 2008 (Pristaulacus), spec. n.townesi Smith, 2008 (Pristaulacus), spec. n.tria Smith, 2008 (Pristaulacus), spec. n.triclora Smith, 2008 (Pristaulacus), spec. n.unimacula Smith, 2008 (Pristaulacus), spec. n.virga Smith, 2008 (Pristaulacus), spec. n.